Drug compliance in children with epilepsy: Cross-sectional study, New Delhi - Verma, Neha; Tripathi, Smita; Sharma, Suvasini (Indian Journal of Child Health, 2016)
Background: For individuals with epilepsy, adherence to medication is crucial in preventing or minimizing seizures and their cumulative impact on everyday life. Compliance studies in adult patients are many, but few in children with epilepsy. Objective: This study tries to find the prevalence of noncompliance in children with epilepsy and causes leading to it. Method: The study was conducted in a tertiary care super specialty children hospital of New Delhi. Children, age 1-12 years, who were already diagnosed cases of epilepsy and were all on drug therapy for at least 3 months were included in the study. After obtaining clearance from the hospital’s Ethical Committee, a total of 100 parents of epileptic children were interviewed as per the prepared questionnaire. Results: Out of 100 children (63 males, 37 females) with epilepsy, 71% were compliant. Most of the noncompliant parents (82.7%) felt that there is the harmful effect of long-term anti-epileptic drugs. They believed in stopping medications on their own once signs and symptoms disappear and did not like to give medication to their child in public place. No significant association of noncompliance could be seen with etiology of epilepsy, monotherapy versus polytherapy, and duration of disease, mother’s age and parental education (p>0.05). Conclusion: Compliance in this study group of children with epilepsy was 71%. Further improvement of health and well-being of children with epilepsy can be attempted by education of parents, distribution of written instructions in the form of pamphlets, counseling, group discussions, and exchange of personal experience. Public awareness drive should help in reducing the associated taboos.